Acidic and Basic pH Effect in Two Cytoplasmic and Endoplasmic Reticulum Luminal Spaces on Chloride Channel Electrophysiological Behavior - Aslanpour Alamdary, Farzaneh; Saghiri, Reza; Ranjbar, Minoo; Namvar Aghdash, Simin (Novelty in Biomedicine, 2018)
Background: In regard of chloride channel electrophysiological behavior importance in cellular homeostasis maintenance, some of diseases appearance because of chloride channels impairment, also reports of synchronization between chloride channels impairment and misadjusted pH and that presumably acid or basic pH in cytoplasmic and endoplasmic reticulum luminal spaces are effective on this behavior, current study was performed. Materials and Methods: Research was performed by experimental method. Vesicles from rat liver tissue endoplasmic reticulum were extracted and assessed in 30 samples in 6 groups. Electrophysiological behaviors of channels were measured in control, acidic and basic pH in cis and Trans environments and according of channel conductance and Po this behavior was determined and judged statistically. Data were filtered at 1 kHz and stored at a sampling rate of 10 kHz for offline analysis by PClamp9. Statistical analysis was performed based on Markov noise free single channel analysis. Results: Channel conductance was 72 pS and its current – Voltage relation curve was linear. Channel has Voltage dependent behavior and has grater Po in positive Voltages. Channel conductance in acidic pH remained at 72 pS as of control situation. Channel Po was not changed. In basic pH these findings were also repeated. Also, in cis and Trans spaces these behaviors were sawed. Conclusion: It seems that in pH stream from 6 to 8.5, current channel electrophysiological behavior could be important in endoplasmic reticulum and cellular homeostasis maintenance especially in positive ion such as calcium ion accumulation situation in cytoplasm.